“Was it for this [. . .]?”: The Poetic Histories of Southey and Wordsworth - Bainbridge, Simon (Romanticism on the Net, 2003)
AbstractThis essay opens with a comparison of Robert Southey’s “History” and William Wordsworth’s The Prelude as poems of poetic dedication at a time of historical crisis. It argues that Southey’s text offers a manifesto for a different poetic mode to the one normally defined as Romantic. Through readings of Southey’s Joan of Arc and Wordsworth’s “The Discharged Soldier”, it examines the contrasting ways in which the two poets responded to the war with France and shows how the conflict played a major role in the shaping of their poetic identities. The writers’ different trajectories as poets are traced through an examination of their poetic dialogue from 1798 to 1802 as Southey countered what is often seen as one of the fundamental manoeuvres that characterizes the development of Wordsworthian Romanticism, the shift from a polemical humanitarian concern with suffering individuals to a psychological interest in their states of mind. Southey’s “The Sailor’s Mother” offered a reassertion of the importance of history so powerful that Wordsworth himself replied to it in a poem of the same name. Yet despite their differences, Southey’s “History” and Wordsworth’s The Prelude illustrate another crucial element of the two writers’ response to historical and vocational crisis during the war, the redefinition of poetry as a manly pursuit after its increasing feminization in the closing decades of the eighteenth century.